Nutrasetikal Sebagai Terapi Komplementer Pada Major Depressive Disorder (MDD) - Era Yesica Damanik; Mirza Junando; Muhammad Fitra Wardhana (CV. Jasa Sukses Abadi, 2023)
Major depressive disorder (MDD) is known as a type of major depression characterized by altered mood, impaired cognitive function, anhedonia (inability to be able to feel pleasure), vegetative disorders such as insomnia, and fatigue or anorexia. Major depressive disorder (MDD) is one of the most common mental disorders worldwide, as well as one of the most disabling. The current treatment is inadequate so that about two-thirds of those treated with first-line antidepressants do not achieve remission. A therapeutic approach using nutraceutical can improve the response to cases of resistance in antidepressants. Nutraceutical is used as the prevention and treatment of various diseases or neurological disorders without or minimal side effects. A therapeutic approach using nutraceutical can improve the response to cases of resistance in antidepressants by targeting neurobiological pathways associated with the pathophysiology of depression. The purpose of writing this article is to find out the nutraceutical that can be consumed as complementary therapies of major depressive disorder (MDD). The source search method is done through the Google Scholar and Pubmed search engines. The results of the search found several nutraceutical, namely Probiotics, Omega-3 Polyunsaturated Fatty Acids (n-3 PUFAs), Vitamin D, S-Adenosylmethionine (SAMe) and Lactobacillus Plantarum HRAL9 have antidepressant activity. Nutraceutical has the potential to be a complementary therapy in effective major depressive disorder (MDD) therapy.